Synchronization of ovulation and subsequent fertility in subestrous buffaloes using a progesterone-based protocol - Ghuman, Sarvpreet Singh (Indian Journal of Dairy Science, 2014)
Ten subestrous buffaloes were administered progesterone release intravaginal insert (Controlled Internal Drug Release, CIDR) for 8 days. On day 7 (day 0: CIDR insertion) and on day 9, all the buffaloes were administered (i.m.) a PGF2α analogue (500µg Cloprostenol sodium) and a GnRH analogue (0.02 mg Buserelin acetate), respectively. Inseminations were carried out on day 10 and thereafter, if required, on day 11. Transrectal ovarian ultrasonography and jugular vein blood sampling was done on various days of protocol. On day 0, ovarian status of the buffaloes revealed the presence of luteal activity (CL diameter: 10.5±1.2 mm, Plasma progesterone: 1.5±0.3 ng/ml). Subsequent to CIDR placement, plasma progesterone concentrations increased (P